Assessment Resistance Potential to Moisture Damage and Rutting for HMA Mixtures Reinforced by Steel Fibers - Ahmed Abbas Saleem; Mohammed Qadir Ismael (Civil Engineering Journal, 2020)
Rutting is mainly referring to pavement permanent deformation, it is a major problem for flexible pavement and it is a complicated process and highly observed along with many segments of asphalt pavement in Iraq. The occurrence of this defect is related to several variables such as elevated temperatures and high wheel loads. Studying effective methods to reduce rutting distress is of great significance for providing a safe and along-life road. The asphalt mixture used to be modified by adding different types of additives. The addition of additives typically excesses stiffness, improves temperature susceptibility, and reduces moisture sensitivity. For this work, steel fibres have been used for modifying asphalt mixture as they incorporated in the specimens by three percentages designated as 0.5, 1.0 and 1.5 % by the weight of asphalt mixture. The evaluation process based on conducting Marshall Test, Compressive strength test, and the wheel tracking test. The optimum asphalt content was determined for asphalt mixture. The results of the Marshall quotient and the index of retained strength of modified mixtures were increased by 44.0 and 17.38% respectively with adding 1.0% of steel fibres compared with the conventional mixture. The rut depth and dynamic stability were determined by using a wheel tracking test at two various testing temperatures of 45 and 55°C and two applied stresses of 70 and 80 psi. Results show that adding 1% of steel fibres to asphalt mixtures is very effective in increase the rutting resistance and reduce moisture damage.